2020
DOI: 10.3390/nu12020314
|View full text |Cite
|
Sign up to set email alerts
|

Safety Evaluations of Single Dose of the Olive Secoiridoid S-(−)-Oleocanthal in Swiss Albino Mice

Abstract: Epidemiological and clinical studies compellingly showed the ability of Mediterranean diet rich in extra-virgin olive oil (EVOO) to reduce multiple diseases such as cancer, cardiovascular diseases, and aging cognitive functions decline. The S-(−)-Oleocanthal (OC) is a minor phenolic secoiridoid exclusively found in extra-virgin olive oil (EVOO). OC recently gained notable research attention due to its excellent in vitro and in vivo biological effects against multiple cancers, inflammations, and Alzheimer’s dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…Several studies suggested that the absorption of toxins in the gastrointestinal tract change the body, relative organs weight, and hematopoietic system as well. [73][74][75][76] The in vivo toxicological studies data revealed no clinical toxic sign of 5000 mg/kg FSE as revealed from behavioral pattern, mortality, body weight, relative vital organs weight, and biochemical analysis. According to the chemical labeling and classification of acute systemic toxicity recommended by OECD, the FSE was given class 5 status (LD50>5,000 mg/ kg) which was the lowest category of toxicity.…”
Section: Dovepressmentioning
confidence: 92%
“…Several studies suggested that the absorption of toxins in the gastrointestinal tract change the body, relative organs weight, and hematopoietic system as well. [73][74][75][76] The in vivo toxicological studies data revealed no clinical toxic sign of 5000 mg/kg FSE as revealed from behavioral pattern, mortality, body weight, relative vital organs weight, and biochemical analysis. According to the chemical labeling and classification of acute systemic toxicity recommended by OECD, the FSE was given class 5 status (LD50>5,000 mg/ kg) which was the lowest category of toxicity.…”
Section: Dovepressmentioning
confidence: 92%
“…All the sectioning and H&E staining has been done at the AML Laboratories (Jacksonville, FL, USA). Briefly, paraffin-embedded tissues were sliced into 5 µm sections and mounted on positively charged slides, dewaxed with xylene, rinsed with alcohol, rehydrated by water and finally, the tissue slides were stained with H&E. Tissues were then dehydrated through ethanol to xylene and coverslipped with Permount [59].…”
Section: Hematoxylin and Eosin Y (Hande) Stainingmentioning
confidence: 99%
“…OC showed high degree of selectivity to cancerous cells and exhibited modest or no cytotoxic effects against the non-tumorigenic cell lines, including the human adult dermal fibroblast HDFa cells [57], human mammary epithelial MCF10A cells [42], human liver LO2 cells [53], murine macrophages J774A.1 cells [55], human fibroblast BJ cells [58], rat fibroblast 3Y1 cells [58], human lung fibroblast IMR90 cells [58] and isolated primary human hepatocytes [52]. Recent single dose acute safety study further suggested the potential safety profile of OC single oral therapeutic dose (10 mg/kg) in Swiss albino mouse model over 14 days of administration [59]. OC inhibited the metastasis of melanoma and hepatocellular carcinoma to lung in mouse tail vein models after iv injection of A431 melanoma and HCCLM3 hepatocellular cancer cells, respectively [52,53].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, interestingly, OC has been already exhibited in vitro and in vivo modulating β-amyloid, tau phosphorylation, and neuroinflammation activities in different models. A recent study showed the high safety profile of OC acute single oral dose in a Swiss albino mice model [ 47 ]. Unfortunately, one of the major obstacles for the application of OC as a prospective nutraceutical are its irritant, pharyngeal pungent, and astringent taste, similar to the NSAID drug-ibuprofen.…”
Section: Discussionmentioning
confidence: 99%